Please look after mom : a novel - Sin, Kyŏng-suk (Vintage Contemporaries, 2011)
When sixty-nine-year-old So-nyo is separated from her husband among the crowds of the Seoul subway station, her family begins a desperate search to find her. Yet as long-held secrets and private sorrows begin to reveal themselves, they are forced to wonder: how well did they actually know the woman they called Mom? Told through the piercing voices and urgent perspectives of a daughter, son, husband, and mother, Please Look After Mom is at once an authentic picture of contemporary life in Korea and a universal story of family love.